Evaluation of the Adiwiyata Program at Junior High School 23 Palembang - Rohib Andrianto Sangia; Andrias Andrias; Efendi Efendi; Afif Alfiyanto; Ida Bagus Benny Surya Adi Pramana (Tarbawi, 2022)
This study aimed to analyze the evaluation of the Adiwiyata program at State Junior High School 23 Palembang. This type of research is field research carried out in the scene or the place where the symptoms being investigated occur. This research approach uses a qualitative approach. Data collection techniques using observation, interviews, and documentation. The data analysis technique used is data analysis technique according to Miles and Huberman, namely data reduction, data presentation, and verification. Evaluation of the Adiwiyata program at State Junior High School 23 Palembang focused on using the CIPP (Context, Input, Process, Product) evaluation. Supporting factors for the Adiwiyata program at 23 Palembang Junior High School, namely 1) a large schoolyard for planting and gardening; 2) the presence of ornamental plants; 3) availability of water channels; 4) availability of waste bank; 5) greenhouse; 6) the presence of a clean water tank; 7) schoolyard using paving blocks; 8) budget funds from the government for the Adiwiyata program; and 9) school residents work together. The factor that hinders the implementation of the Adiwiyata program at SMPN 23 Palembang is the COVID-19 pandemic, where students cannot participate in the Adiwiyata program activities at their schools. In addition, students lack awareness of the environment, so teachers must provide education and socialization to them about Adiwiyata to create healthy schools that care about the environment.